Release of Infectious Epstein-Barr Virus by Transformed Marmoset Leukocytes - Miller, George (1973)
Marmoset blood leukocytes transformed in vitro by Epstein-Barr virus regularly release extracellular infectious Epstein-Barr virus with high titers of transforming activity. By comparison, human umbilical cord leukocytes and adult human leukocytes transformed by Epstein-Barr virus release either no extracellular infectious virus or small amounts, irregularly.